The Effect of Music Listening on Anxiety Levels in Post-Subarachnoid Block Anaesthesia Patients - Prandani, Muhammad Yogi; Kurniawaty, Juni; Apsari, Ratih Kumala Fajar (Jurnal Komplikasi Anestesi, 2025)
Background: The patients’ perioperative conditions can affect post-operative anxiety. Subarachnoid block anaesthesia can increase the incidence of post-operative anxiety. Methods to reduce post-operative anxiety are divided into pharmacological, with the administration of sedative drugs, and non-pharmacological, with holistic education, acupuncture, listening to music during surgery, and othersObjective: This study aims to observe the effect of listening to music on the anxiety level of surgical patients undergoing subarachnoid block anesthesia.Methods: This study was a Randomized Controlled Trial (RCT), with an intervention group (n=50) listening to music after subarachnoid block during surgery and a control group (n=50) receiving standard routine anesthetic care. Anxiety assessment using the STAI score and vital signs were performed at 3 different times in both groups.Results: There were no differences in patient characteristics between the two groups. Anxiety measurement in the reception room (X1) showed 37 patients (74%) and 31 patients (62%) with moderate anxiety in the intervention and control groups, respectively (p>0.05). There was no difference in patient anxiety levels between the two groups (p>0.05) in the operating room (X2). Post-operative anxiety measurement in the recovery room (X3) showed 43 patients (86%) with low anxiety in the intervention group, compared to 32 patients (64%) in the control group. Patients who listened to music during surgery had a lower level of post-operative anxiety compared to the control group (p=0.011). Conclusion: Listening to music can reduce post-operative anxiety in patients undergoing surgery with subarachnoid block, compared to patients receiving standard routine care